Making fruit leather pineapple fruit (ananas comosus l) subgrade with the addition of red dragon fruit skin (hylocereus costaricensis) - Muhammad Zulfan Nuroni Pulungan; Wendianing Putri Luketsi; Devi Urianty Miftahul (Universitas Darussalam Gontor, 2020)
Fruit leatheris a fruit preserved product that is still able to maintain the taste of the raw materials used. This study aims to obtain the right formulation between subgrade pineapple puree and red dragon fruit peel puree that affect the characteristics of fruit leather. The design of this study used a Completely Randomized Design (CRD) with 3 treatment levels of concentration between subgrade pineapple puree and red dragon fruit puree with a ratio of 80% and 20%, 85% and 15%, 90 and 10%, respectively. The total pureeused was 400 g in each treatment, then 0.6% carrageenan and 8% sorbitol were added. Each treatment was repeated 3 times so that a total of 9 experimental units was obtained. The data generated was then analyzed using ANOVA and continued with the Duncan test. The results showed that each treatment had a significant effect on antioxidant activity, and had a non-significant effect on water content, total sugar, total acid, and organoleptics (color, taste, texture, aroma and overall). Based on the hedonic test(overall), the best research results were obtained in F1 treatment (80% puree of pineapple fruit and 20% puree of dragon fruit skin) with a moisture content of 9.5%, total acid of 1.46%, total sugar of 36.25% antioxidant activity 73.93%